A framework proposal to set the ‘Ground Rule Book’ effectively and enhance mutual understanding in the context of engineering education for India - Biswal, Aparajita; Rajyaguru, Hemalkumar; Patel, Vimalkumar N.; Gandhi, Vaibhav; Jadeja, Sidhharthsinh (Journal of Engineering Education Transformations, 2025)
Previously, we were aware of the fact that a Ground rule book is a set of articulated points which induce the expected behaviour of a student inside the classroom. In the earlier decade of the 21st century, the ground rules were set generally by the faculties instead of involving the students themselves in setting the rules. The survey shows, that the students’ try to adhere to the rules increases as they play a role in creating or designing the framework for it. This study shows an analysis report on qualitative research on setting the ground rule book practice for the last three years in the teaching-learning process. In this paper, the various parameters of ground rules and their outcomes are discussed. The parameters are identified by discussing and interviewing the student leaders of each year and the applicability of the ground rules is also verified by the teaching faculty to prepare the analysis report.